Enhancing riverine load prediction of anthropogenic pollutants: Harnessing the potential of feed-forward backpropagation (FFBP) artificial neural network (ANN) models - Khairudin, Khairunnisa; Ul-Saufie, Ahmad Zia; Senin, Syahrul Fithry; Zainudin, Zaki; Rashid, Ammar Mohd; Abu Bakar, Noor Fitrah; Anas Abd Wahid, Muhammad Zakwan; Azha, Syahida Farhan; Abd-Wahab, Firdaus; Wang, Lei; Sahar, Farisha Nerina; Osman, Mohamed Syazwan (Results in engineering, 2024)
Assessing riverine pollutant loads is a more realistic method for analysing point and non-point anthropogenic pollution sources throughout a watershed. This study compares numerous mathematical modelling strategies for estimating riverine loads based on the chosen water quality parameters: Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Suspended Solids (SS), and Ammoniacal Nitrogen (NH3–N). A riverine load model was developed by employing various input variables including river flow and pollutant concentration values collected at several monitoring sites. Among the mathematical modelling methods employed are artificial neural networks with feed-forward backpropagation algorithms and radial basis functions. The classical multiple linear regression (MLR) statistical model was used for the comparison. Four widely used statistical performance assessment metrics were adopted to evaluate the performance of the various developed models: the root mean square error (RMSE), mean absolute error (MAE), mean relative error (MRE), and coefficient of determination (R2). The considerable number of errors (with RMSE, MAE, and MRE) discovered in estimating riverine loads using the multiple linear regression (MLR) statistical model can be attributed to the nonlinear relationship between the independent variables (Q and Cx) and dependent variables (W). The feed-forward neural network model with a backpropagation algorithm and Bayesian regularisation training algorithm outperformed the radial basis neural network. This finding implies that, in addition to suspended sediment loads, riverine loads may be predicted using an artificial neural network using pollutant concentration (Cx) and river discharge (Q) as input variables. Other geographical and temporal fluctuation characteristics that may impact river water quality, on the other hand, may be incorporated as input variables to enhance riverine load prediction. Finally, riverine load analyses were successfully conducted to reduce the riverine load. •Assessing pollutant load accurately evaluates pollution sources in a watershed.•Artificial neural networks were used to predict riverine loading.•Riverine load model built with discharge & pollutant data from monitoring stations.•Feed-forward neural network with Bayesian Regularisation training is superior to radial basis function and MLR.•The developed riverine load prediction model aids in assigning load reduction allocations.